Improving Students' Creativity Through Modern Puppet Project Learning Model in Senior High School - Rendhy Galih Prayogo; Indro Moerdisuroso; Aprina Murwanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve students' creativity through the application of project-based learning models (PjBL) with modern puppet media in fine arts subjects at the Senior High School (SMA) level. The background of this study is based on the low creativity of students due to the conventional approach to fine arts learning and the lack of integration of media and technology in learning. The study was conducted as Classroom Action Research (CAR) with a descriptive qualitative approach implemented in class XI of SMA Negeri 46 Jakarta. Data collection techniques were carried out through observation, interviews, documentation, learning outcome tests, and questionnaires. The results of the study showed that the application of project-based learning models with modern puppet media significantly increased teacher and student activity in the learning process, improved learning outcomes, and received positive responses from students. Modern puppets have proven to be an effective medium in stimulating imagination, strengthening local cultural values, and building student character. This study recommends the use of creatively modified traditional media as an educational tool in developing student creativity in the era of the independent curriculum. The results of the study showed that the application of project-based learning models with modern puppet media significantly increase teacher and student activities in the learning process, improve learning outcomes, and receive positive responses from students. Modern puppets have proven to be an effective medium in stimulating imagination, strengthening local cultural values, and building student character. This study recommends the use of creatively modified